2016
DOI: 10.1097/phm.0000000000000502
|View full text |Cite
|
Sign up to set email alerts
|

How Do Recurrent and First-Ever Strokes Differ in Rehabilitation Outcomes?

Abstract: : The Association of Academic Physiatrists is accredited by the Accreditation Council for Continuing Medical Education to provide continuing medical education for physicians. The Association of Academic Physiatrists designates this activity for a maximum of 1.5 AMA PRA Category 1 Credit(s)™. Physicians should only claim credit commensurate with the extent of their participation in the activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…These patients may differ in the amount of pre-stroke comorbidities, as comorbidity is suggested to negatively influence outcome [ 36 ]. In addition, research by Ng and colleagues found that patients with multiple infarcts show spontaneous neurobiological recovery to a lesser extent than patients with a first-ever stroke [ 37 ], suggesting that quality of vascularization is an important issue for recovery. Contrary, a recent prospective cohort study did show that patients with previous or hemorrhagic strokes may also show proportional recovery of the upper extremity [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…These patients may differ in the amount of pre-stroke comorbidities, as comorbidity is suggested to negatively influence outcome [ 36 ]. In addition, research by Ng and colleagues found that patients with multiple infarcts show spontaneous neurobiological recovery to a lesser extent than patients with a first-ever stroke [ 37 ], suggesting that quality of vascularization is an important issue for recovery. Contrary, a recent prospective cohort study did show that patients with previous or hemorrhagic strokes may also show proportional recovery of the upper extremity [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of baseline characteristics between the ICH and IS groups revealed that ICH group had a lower proportion of previous stroke (8.7% vs 22.5%, p=0.02). Since recurrent stroke patients make less functional gains compared with first-ever stroke patients, 38 we excluded patients with previous strokes to avoid the confounding effect, and the ICH group still had greater total BI improvement than the IS group (30 vs 25 , p=0.02); the BI improvement at the late phase of PAC was also greater in the ICH group (ΔBI 6w-final : 12.5 [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] vs 10 [0-20], p=0.02) ( Table 3).…”
Section: Patients Who Had First-ever Strokementioning
confidence: 99%
“…1,2 The annual cost of stroke in Europe is estimated to be €20 billion for direct care, €16 billion for informal care and €9 billion due to loss of productivity. 3 Recurrent major cardiovascular events occur in more than 12% of patients over five years, even in patients receiving excellent evidence-based treatment in affluent countries 4 and are associated with poor rehabilitation outcomes, 5 physical disability and cognitive dysfunction. 6 Optimal provision of secondary prevention has the potential to reduce recurrent events by up to 80%, 3 but this requires rapid assessment, appropriate treatment and ongoing follow-up to ensure efficacy and adherence to treatments.…”
Section: Introductionmentioning
confidence: 99%